Opportunities and challenges of community-based rural drinking water supplies: An analysis of water and sanitation committees in Ghana - Sun, Yan; Asante, Felix A.; Birner, Regina (International Food Policy Research Institute, 2010)
Providing safe drinking water in rural areas is a major challenge because it is not easy to establish institutional arrangements that will ensure that drinking water facilities are provided, maintained, and managed in an efficient, equitable, and sustainable way. Like many other countries, Ghana has adopted a community-based approach to meet this challenge. Community-based water and sanitation committees (WATSANs) are in charge of managing drinking water facilities at the local level. They are supported by water and sanitation teams of each district administration and by the Community Water and Sanitation Agency, an independent agency that has been created to facilitate the community-based approach. This paper is based on the analysis of two survey datasets of WATSANs and households in rural Ghana. The paper confirms some findings of the earlier literature on this topic. For example, communities that have a higher level of existing community groups are more likely to have functioning WATSANs, while ethnically diverse communities are less likely to have these organizations. The paper also indicates that WATSANs have a positive effect on the mobilization of payment for water services. Using empirical data on local leaders, the paper shows that leadership also matters for the provision of safe drinking water. In particular, the paper suggests that female leaders seem to be effective in this respect.